Analisis Modifikasi Diameter Lubang Intake Manifold Terhadap Performa Sepeda Motor 160 Cc Menggunakan Bahan Bakar Pertamax 92 - Pratama, Aditya Wahyu; Imam, Ahmad Fikrih Saiful; Budiprasojo, Azamataufiq (Jurnal Teknik Terapan, 2025)
The performance of a motorcycle engine is influenced by the efficiency of the air and fuel intake system, where the intake manifold hole diameter plays a crucial role in regulating airflow into the combustion chamber. This study aims to analyze the effect of modifying the intake manifold hole diameter on the performance of a 160 cc motorcycle using Pertamax 92 fuel. The research method involved an experiment by performing porting and polishing on the intake manifold to reduce turbulence. The tested hole diameter variations were 26 mm (standard), 27.50 mm, and 28.50 mm. The test results showed that a 27.50 mm diameter produced the best performance with a torque of 11.50 Nm (4000 rpm), 11.65 Nm (5000 rpm), and 11.92 Nm (6000 rpm). The engine power also increased with results of 11.4 Hp (4000 rpm), 11.5 Hp (5000 rpm), and 11.8 Hp (6000 rpm). The 27.50 mm diameter was proven to provide an optimal balance between torque and power at various engine speeds.